2017
DOI: 10.1210/jc.2017-00354
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors, Nephropathy, and Cardiovascular Disease in Type 2 Diabetes: The Fremantle Diabetes Study

Abstract: Although PPI use was not associated with a sustained adverse effect on uACR, the association between PPI initiation and both worsening nephropathy and increasing 5-year CVD risk has potential clinical implications in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Nevertheless, those studies did not take into account the severity of diabetes, such as HbA1c, duration of diabetes, and oral drugs/insulin use. To our best knowledge, there is only one prospective study that investigated the association of PPIs use and CVD risk among 1732 patients with T2D with an average of 2.1 years of follow-up [29]. In line with the previous study, our study also showed PPIs use was associated with higher risk of CVD, as well as all-cause mortality.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, those studies did not take into account the severity of diabetes, such as HbA1c, duration of diabetes, and oral drugs/insulin use. To our best knowledge, there is only one prospective study that investigated the association of PPIs use and CVD risk among 1732 patients with T2D with an average of 2.1 years of follow-up [29]. In line with the previous study, our study also showed PPIs use was associated with higher risk of CVD, as well as all-cause mortality.…”
Section: Discussionsupporting
confidence: 89%
“…Patients with T2D are at more than three times higher prevalence of using PPIs [27], and two-to fourfold higher risk of developing cardiovascular complications and premature death than general populations [28]; however, the evidence regarding the in uence of PPIs use on subsequent risks of CVD and mortality among patients with T2D is scarce. To our best knowledge, only one prospective study from Australia showed PPI initiation was associated with a higher risk of 5-year CVD risk among patients with T2D [29]. However, the previous study had a sample size of 1732, a mean follow-up period of 2.1 years, and only a composite CVD outcome; further studies with larger sample size, longer follow-up period, and a closer investigation of CVD subtypes are needed.…”
Section: Introductionmentioning
confidence: 97%
“…The inhibition of the efficacy of clopidogrel could increase the risk of thromboembolism and coronary syndrome [25]. Because of impaired vasodilation and ischemic changes associated with PPIs, a number of previous studies have demonstrated an increased risk of cardiovascular diseases related to PPI use [26,27]. A review study described that PPI use was related to excess mortality from cardiovascular diseases in 15/1000 persons [27].…”
Section: Discussionmentioning
confidence: 99%
“…These include the use of vitamin B12 supplementation and proton pump inhibitor (PPI) therapy. The use of PPIs is common in type 2 diabetes, 17 and they have the potential to interact with metformin to increase the risk of B12 deficiency by further reducing absorption 18 . In addition, almost all studies published to date have assessed deficiency from total vitamin B12 concentrations rather than measurement of the transcobalamin–vitamin B12 complex (holotranscobalamin), which represents the biologically active form taken up through specific cell surface receptors 19 .…”
Section: Introductionmentioning
confidence: 99%